Determination of chemoresistance of ovarian cancer cells in vitro - K. A. Kuzin; T. I. Fetisov; R. I. Knyazev; L. Ya. Fomina; L. V. Meheda; E. A. Lesovaya; G. A. Belitsky; M. G. Yakubovskaya; K. I. Kirsanov (Успехи молекулярной онкологии, 2019)
Objectives: to provide a rationale for existing approaches for the evaluation of chemoresistance of ovarian cancer in vitro, to perform a comparative analysis of the methods and to assess the perspectives of their further application.Materials and methods. For the review preparation, we analyzed articles on experimental testing of ovarian cancer resistance to chemotherapeutic agents, available at biomedical literature databases SciVerse Scopus (158), PubMed (323), Web of Science (285), RSCI (64). The review cited 37 recent publications, 12 of them being published over the past three years, and 16 articles being referred as pioneer publications on techniques previously and used today.Results. Peculiarities of the main methods for assessing the resistance and sensitivity of a cancer to various chemotherapeutic drugs using primary cultures of tumor cells obtained from biopsy or surgical material are analyzed. Proliferative and metabolic activities as well as the level of cell death were considered as the main evaluated characteristics of tumor cells. The methodological features of the described methods are discussed, as well as the prospects for their further application.Conclusion. Predictive detection of chemoresistance of ovarian cancer is based on testing the viability of tumor cells in the presence of a chemotherapeutic drug. The results of studies of the key mechanisms of chemoresistance development in tumor cells provide the rationale for improving in vitro testing.